KNOWLEDGE, ATTITUDE, AND PRACTICE REGARDING OVER-THE-COUNTER MEDICINE AND SELF-MEDICATION AMONG STUDENTS AT MEDICARE HEALTH PROFESSIONALS COLLEGE. A CROSS-SECTIONAL STUDY. - INGABIRE , MOUREEN; ANYWAR, LYDIA (Student's Journal of Health Research Africa, 2024)
Study objectives: The general objective of this study was to assess the Knowledge, Attitude, and Practice of self-medication and over-the-counter medicine use while the specific objectives were to assess the knowledge, attitude, and practice self-medication and use of over-the-counter medications among students of Medicare health Professionals College. Methodology: A descriptive cross-sectional study was conducted with data collected from 115 respondents selected by simple random sampling using printed self-administered questionnaires. The data was then analyzed using Microsoft Excel version 2010 and presented in tables, pie charts, and graphs. Results: Out of 115 respondents, 99(86%) knew that the use of medicines with unknown substances was dangerous to people with liver and kidney diseases, and 58(50%) of them got information from the internet and social media. About 113(98%) thought that self-medication was part of self-care, 82(71%) thought self-medication was acceptable, 94(82%) had practiced self-medication only once in the past 3 months, 40(35%) practiced self-medication because they had a headache, 10(45%) adjusted the dose because of not getting better. Conclusion: The majority of the students had considerable knowledge concerning self-medication and the majority had self-treated themselves for mild health conditions. The internet and social media were the most used sources of information among the students. However, their attitude about the safety and effectiveness of self-medication and over-the-counter medicines is not satisfactory. Recommendations: The government and other concerned stakeholders should have a more intense sensitization of the general population about mindset change and advice on how to safely practice self-medication. Health promotion and sensitization campaigns should also be channeled to the internet and social media since is the audience mostly used by youths in the country.